Real‐world data on treatment concepts in classical Hodgkin lymphoma in Sweden 2000–2014, focusing on patients aged >60 years. Issue 3 (6th May 2021) - Wahlin, Björn Engelbrekt; Övergaard, Ninja; Peterson, Stefan; Digkas, Evangelos; Glimelius, Ingrid; Lagerlöf, Ingemar; Johansson, Ann‐Sofie; Palma, Marzia; Hansson, Lotta; Linderoth, Johan; Goldkuhl, Christina; Molin, Daniel
Abstract: Treatment for patients > 60 years with classical Hodgkin lymphoma (cHL) is problematic; there is no gold standard, and outcome is poor. Using the Swedish Lymphoma Registry, we analysed all Swedish patients diagnosed with cHL between 2000 and 2014 ( N  = 2345; median age 42 years; 691 patients were >60 years). The median follow‐up time was 6.7 years. Treatment for elderly patients consisted mainly of ABVD or CHOP, and the younger patients were treated with ABVD or BEACOPP (with no survival difference). In multivariable analysis of patients > 60 years, ABVD correlated with better survival than CHOP ( p  = 0.027), and ABVD became more common over time among patients aged 61–70 years ( p  = 0.0206). Coinciding with the implementation of FDG‐PET/CT, the fraction of advanced‐stage disease increased in later calendar periods, also in the older patient group. Survival has improved in cHL patients > 60 years ( p  = 0.027), for whom ABVD seems superior to CHOP.